PERANCANGAN BUKU PENGENALAN REPTIL IGUANA HIJAU BERBASIS FOTOGRAFI SEBAGAI SARANA INFORMASI BAGI MASYARAKAT SURABAYA - Anggara, Fredian Dwi; Riyanto, Darwin Yuwono; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The purpose of designing a book based green iguana reptile introduction of photography as a means of information for the people of Surabaya. To introduce and provide a knowledge of the green iguana reptiles, and also provides maintenance information reptile green iguana well. Further studies conducted using qualitative research methods are observation, interviews, documentation, and literature. To obtain the data used and supports the creation of a book-based green iguana reptile introduction of photography as a means of information for the people of Surabaya. Data were analyzed using multiple stages, namely data reduction, data presentation and conclusion. After analyzing the data, found a book concept based green iguana reptile introduction of photography as a means of information for the people of Surabaya. Keyword "Beauty", the description of "beauty" is a state of unsightly nature and character of a person, place, object, or idea that provides perceptual experience of pleasure, meaning, or satisfaction. An entity that is admired, has a feature that is associated in perfection. The concept of "beauty" aims to show that the Green Iguana Reptile are exotic animals and pets can be. Keywords: Books Introduction, Based Photography, Green Iguana Reptile.